Polymerase chain reaction for the amplification of the 121-bp repetitive sequence of Schistosoma mansoni: a highly sensitive potential diagnostic tool for areas of low endemicity. Issue 6 (November 2015) - Ferrer, E.; Pérez, F.; Bello, I.; Bolívar, A.; Lares, M.; Osorio, A.; León, L.; Amarista, M.; Incani, R.N.
Abstract Schistosomiasis is a disease caused by parasitic flatworms of the genus Schistosoma, whose diagnosis has limitations, such as the low sensitivity and specificity of parasitological and immunological methods, respectively. In the present study an alternative molecular technique requiring previous standardization was carried out using the polymerase chain reaction (PCR) for the amplification of a 121-bp highly repetitive sequence for Schistosoma mansoni. DNA was extracted from eggs of S. mansoni by salting out. Different conditions were standardized for the PCR technique, including the concentration of reagents and the DNA template, annealing temperature and number of cycles, followed by the determination of the analytical sensitivity and specificity of the technique. Furthermore, the standardized PCR technique was employed in DNA extracted, using Chelex®100, from samples of sera of patients with an immunodiagnosis of schistosomiasis. The optimal conditions for the PCR were 2.5 mm MgCl2, 150 mm deoxynucleoside triphosphates (dNTPs), 0.4 μm primers, 0.75 U DNA polymerase, using 35 cycles and an annealing temperature of 63°C. The analytical sensitivity of the PCR was 10 attograms of DNA and the specificity was 100%. The DNA sequence was successfully detected in the sera of two patients, demonstrating schistosomiasis transmission, although low, in the community studied. The standardized PCR technique, using smaller amounts of reagents than in the original protocol, is highly sensitive and specific for the detection of DNA from S. mansoni and could be an important tool for diagnosis in areas of low endemicity.